Effects of Liupao Tea with Different Years of Aging on Glycolipid Metabolism, Body Composition, and Gut Microbiota in Adults with Obesity or Overweight: A Randomized, Double-Blind Study - Yuyang Wang; Qiang Hu; Botian Chen; Defu Ma (Foods)
Background: Liupao tea (LPT) is a traditionally fermented dark tea from Guangxi, China and the effects of different aging periods of LPT on metabolic health remain inadequately explored. Methods: This randomized, double-blind, longitudinal study enrolled 106 adults with obesity or overweight who were assigned to consume LPT of different ages over a 90-day period. Participants were randomly divided into four groups, each consuming LPT that had been aged for 1 year, 4 years, 7 years, or 10 years. The metabolic parameters, body composition, and gut microbiota were assessed at baseline and after the 90-day intervention. Results: All LPT groups experienced significant reductions in systolic blood pressure (SBP) and diastolic blood pressure (DBP), with the 10-year-aged group showing the most notable SBP decrease (p < 0.001). Total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) levels decreased significantly in the 1-, 4-, and 10-year-aged groups (p < 0.05), while high-density lipoprotein cholesterol (HDL-C) increased in the 7-year-aged group (p < 0.05). Body weight, body fat mass (BFM), body mass index (BMI), waist circumference (WC), body fat percentage (BFP), and visceral fat area (VFA) significantly declined across all groups (p < 0.05). Gut microbiota analysis showed changes in specific genera, though overall diversity remained stable. No significant differences were found in metabolic or microbiota outcomes between the different aged groups. Conclusions: LPT consumption effectively improves blood pressure, lipid profiles, and body composition in adults with obesity without adverse liver effects. The aging duration of LPT does not significantly alter these health benefits, challenging the belief that longer-aged LPT is superior.